2014
DOI: 10.1007/s00299-014-1647-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of WRKY genes in di-haploid Populus simonii × P. nigra in response to salinity stress revealed by quantitative real-time PCR and RNA sequencing

Abstract: Spatio-temporal expression patterns of 13 out of 119 poplar WRKY genes indicated dynamic and tissue-specific roles of WRKY family proteins in salinity stress tolerance. To understand the expression patterns of poplar WRKY genes under salinity stress, 51 of the 119 WRKY genes were selected from di-haploid Populus simonii × P. nigra by quantitative real-time PCR (qRT-PCR). We used qRT-PCR to profile the expression of the top 13 genes under salinity stress across seven time points, and employed RNA-Seq platforms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 41 publications
5
22
0
Order By: Relevance
“…r-project.org/) as Wang et al (2014) reported. Single variable analysis was used to compare the overall gene expression of the 13 genes at each of the time points (with Plant Growth Regul PEG-6000 or ABA treatment) to the control (without treatment), and to compare the overall gene expression between the tissues.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…r-project.org/) as Wang et al (2014) reported. Single variable analysis was used to compare the overall gene expression of the 13 genes at each of the time points (with Plant Growth Regul PEG-6000 or ABA treatment) to the control (without treatment), and to compare the overall gene expression between the tissues.…”
Section: Discussionmentioning
confidence: 75%
“…The difference values of CT (dCT) between a sample and the average of the the three house-keeping genes (ACT, EF1 and UBQ) as the expression level of the sample. Therefore, the higher the dCT value, the lower expression of mRNA in the sample, and vice versa (Wang et al 2014). …”
Section: Rna Extraction and Qrt-pcr Analysismentioning
confidence: 97%
See 3 more Smart Citations